Land for the people : the state and agrarian conflict in Indonesia - Lucas, Anton E.; Warren, Carol; Lucas, Anton E. (Research in international studies. Southeast Asia series ;, 2013)
"Half of Indonesia's massive population still lives on farms, and for these tens of millions of people the revolutionary promise of land reform remains largely unfulfilled. The Basic Agrarian Law, enacted in the wake of the Indonesian Revolution, was supposed to provide access to land and equitable returns for peasant farmers. But fifty years later, the law's objectives of social justice have not been achieved. Land for the People provides a comprehensive look at land conflict and agrarian reform throughout Indonesia's recent history, from the roots of land conflicts in the prerevolutionary period, and the Sukarno and Suharto regimes, to the present day, in which democratization is creating new contexts for peoples' claims to the land. Drawing on studies from across Indonesia's diverse landscape, the contributors examine some of the most significant issues and events affecting land rights, including shifts in policy from the early postrevolutionary period to the New Order; the Land Administration Project that formed the core of land policy during the late New Order period; a long-running and representative dispute over a golf course in West Java that pitted numerous indigenous farmers in Kalimantan against the urban elite; Suharto's notorious "million hectare" project that resulted in loss of access to land and resources for numerous farmers; and the struggle by Bandung's urban poor to be treated equitably in the context of commercial land development. Together, these essays provide a critical resource for understanding one of Indonesia's most pressing and most influential issues"--